Dancing with atrial fibrillation - How arrhythmia affects everyday life of family members: A qualitative study. - Stine Rosenstrøm (Public Library of Science (PLoS), 2021)
Background Atrial fibrillation (AF) is the most common cardiac arrhythmia. Patients with AF often experience debilitating symptoms, stress and reduced health-related quality of life. Previous qualitative research on AF has primarily focused on the patient. AF, however, can also be burdensome for the patient's family. Aim The aim of this study was to explore how family members experience life when a close member in the family has AF. Method Transcribed focus group interviews were analysed using content analysis approach inspired by Graneheim and Lundman. Results Two focus group interviews were conducted with 11 family members. The overall theme was Dancing with AF. The theme emerged from three categories: 1) Handling AF as a living condition, 2) Influencing the roles of family members, 3) Fear of AF attack. AF had a very significant impact on the patients' family members, forcing them to reconstruct their daily lives. Conclusions AF has multiple consequences for family members and can give rise to conflicts concerning family roles. Family members have a lack of knowledge of AF and fear of how AF can cause changes in the family members' everyday lives. This study demonstrates that there is a need for further research of ways to support the family members of patients with AF.